Pemetaan Potensi Energi Surya Berbasis Global Solar Atlas di Fakultas Teknik Universitas Mataram - Supriyatna Supriyatna; Natsir Abdul; Seniari Ni Made; Adnyani Ida Ayu Sri; Nababan Sabar (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2024)
Indonesia the average global horizontal irradiation value is 4,75 kWh/m2 per day. Because Indonesia is on the equator. This energy potential has great opportunities for application in off-grid and microgrid PV systems. Global solar atlas is a free web-based application developed to help policymakers, planners, and investors identify areas of solar radiation intensity for solar power generation virtually anywhere in the world. The coordinate points for irradiation measurements in the yard of the Faculty of Engineering, University of Mataram using a Solar Power Meter (SPM) at coordinates -8.5880530, 116.0976210. The measurement position of an azimuth angle of 0 degrees and a solar panel tilt of 12 degrees is the optimum global irradiation of 1930.2 kWh/m2 per year. The potential for PLTS rooftops at the Faculty of Engineering, the total PV panels have the potential to be installed on the rooftop as many as 2,283 (300 Wp per PV panel), the total power of the PV panels is 684,900 Wp or 684.9 kWp. Based on the Global solar atlas, the total potential energy that can be generated by all PV panels in the North and South directions is 882.9 MWh/year